Investigating The Stakeholders' Attitudes Towards Prioritizing Agile Project Management Strategies as A Change Management Tool in Construction Projects - Shafie, Basma Ahmed Eid; Meselhy, Mohammed Saeed; Elattar, Sherif Mohamed Sabry (International Journal of Membrane Science and Technology, 2023)
Construction projects face several problems in order to achieve their goals (time – cost – quality) especially since it has many inputs such as materials, labor and machinery. Measuring these goals in the money language is the key to their integration, so reducing costs is an important aspect of any project. One of the ways to reduce costs is to focus on how to avoid implementation problems and the financial implications of it. Several factors including irregular financial flows, poor management due to the lack of programs that support the administrative awareness of projects, financial and administrative instability, poor control and supervision, unskilled labor, insufficient machinery, inappropriate timing for the arrival of materials, changes in the construction conditions, lack of clarity of specifications, insufficient preparation during the pre-implementation stages, imposed regulations and laws, and other factors that contribute to problems in the implementation of major national projects. This study aimed to enhance the general understanding concerning the factors that affect the adoption of APM strategies in construction industry. The research relied on the inductive-analytical approach through conducting a questionnaire among stakeholders to analyze major development construction projects which can be benefited from applying the concept of agility to reduce project failure, then presenting and analyzing results of the survey questionnaire conducted with a sample of Egyptian design and construction firms to investigate their perception and application of prioritizing agile project management strategies as a change management tool in construction. The results of the thesis suggested that the Agile methodology is likely to yield significant benefits, primarily characterized by enhanced client engagement. The Agile approach significantly encourages increased customer engagement in the project as opposed to the current scenario. Additionally, it has the potential to reduce uncertainty and enhance risk management. The implementation of time management techniques and regular meetings is advantageous in monitoring the development and status of the project.